The Effect of Implementing the VIRLEP LMS Learning Media on Students' Critical Thinking Abilities - Novita Dwi Novita Novita; Yayuk Chayatun Machsunah; Sutarum (The Future of Education Journal, 2025)
This study examines the low critical thinking abilities of students at SMP Negeri 5 Lamongan, which is caused by conventional teaching methods and the limited use of interactive digital media. The purpose of this research is to test the effect of the VIRLEP LMS (Virtual Learning Environment for Pancasila Education) on students' critical thinking abilities. The research design uses a descriptive quantitative quasi-experiment approach with control and experimental groups, involving 64 seventh-grade students. The instruments used were 15 multiple-choice questions for pretest and posttest. Data analysis was conducted using independent and paired sample t-tests with SPSS 26. The results show no significant difference in initial abilities between the groups (p=0.948), but there was a significant improvement in critical thinking skills in the experimental group compared to the control group (p=0.000). The experimental group had a t-value of 29.728, which is higher than the control group's t-value of 13.190. The conclusion of the study states that the application of the VIRLEP LMS effectively enhances student engagement and critical thinking abilities through interactive features such as videos, quizzes, games, and discussions. It is recommended that the intervention duration be extended to observe long-term effects. The Pancasila-based LMS serves as an innovative learning media alternative to improve the quality of education.